My painting aims to arrive to the texture of the stone, of a tree, or of the water (2014)
Kindi Llajtu has been working with the footprints he finds along and the ones he himself produces and leaves behind as he intervenes upon space, bodies and surfaces. Recovering the traces of the Inga people to which he belongs, their ancient objects, foods, feasts, so as to bring them a new vivacity or make them vanish in a new manner, is a means of generating and playing with the textures of memory that cover and uncover everything; making textures as evidences of time´s flow and its ghosts, polishing, weaving and transforming it all.